Legal Responsibility of Livestock Owners for Crop Damage: An Analysis of Article 84 (1) Qanun No. 3/2013 in Pidie Jaya - Alvi Farisyi; M. Syuib; Muhammad Iqbal; Ming Chou Liu (al-Battar: Jurnal Pamungkas Hukum, 2026)
The formulation of qanun as a regional legal product should not only regulate administrative matters but also accommodate the living law within society. Article 84 paragraph (1) of Qanun of Pidie Jaya Regency Number 3 of 2013 recognizes that disputes related to livestock and animal health may be resolved through customary mechanisms. However, this recognition raises normative problems because it is not accompanied by clear regulations regarding implementation mechanisms, institutional integration, or the legal status of customary dispute settlements within the formal legal system. From the perspective of legal pluralism theory and legal norm theory, this condition indicates that the provision remains declarative rather than operational. This study aims to analyze the normative construction of the article and formulate a more operational normative reconstruction. The research employs a normative legal method using statutory and conceptual approaches. The findings show that Article 84 paragraph (1) does not regulate dispute settlement procedures, coordination between customary institutions and regional government authorities, or the legal consequences of customary settlement outcomes. Consequently, its effectiveness relies more on the social legitimacy of customary law than on formal legal structures. This study proposes a normative reconstruction emphasizing procedural clarity, documentation of customary deliberations, and institutional integration to strengthen legal certainty and harmonization between state law and customary law.